Morphological and structural characteristics of zein biofilms with added xanthan gum - de Almeida, Crislene Barbosa [UNESP]; Catelam, Kelly Tafari [UNESP]; Cornélio, Marinônio Lopes [UNESP]; Filho, José Francisco Lopes [UNESP] (My University, 2010)
Morphological and structural characteristics of zein-based biofilms have been studied in this work. The sorbitan component in the control formulation of the film was substituted with xanthan gum at concentrations between 0.01 and 0.04 % to analyze its effect on lipid dispersion. Scanning electron microscopy (SEM) showed a surface for the control (0 % xanthan) with good lipid distribution. However, when the samples were investigated by optical microscopy (OM), lipid globules in the control biofilm appeared larger and more dispersed in the matrix than in the other samples. Fourier transform infrared (FTIR) spectroscopy indicated that xanthan concentrations deeply affected C=O linkages from amide I group, as well as the functional N-H group of amide II of the zein structure. Other weak interactions of amide I and II with carboxylic acids and aliphatic compounds were also observed. UV/VIS analysis as well as transparency measurements indicated that the addition of xanthan to the film matrix lowered significantly its transparency properties. Overall, the addition of xanthan gum favoured lipid dispersion in the matrix, making biofilms more homogeneous, although less transparent.
Keywords: Morphological properties; Structural properties; Xanthan gum; Zein biofilms